Calculation of a cylindrical surface that ensures a constant traction force or a constant amount of pressure of a material particle that moving through on it at a constant speed - Pylypaka, S. F.; Nesvidomin, A. V. (Energy and Automation, 2023)
On gravitational surfaces and curves, the movement of a particle is determined by the force of its weight. The speed of movement along the curve in such cases is variable. However, in agricultural machines, there may be cases when a particle moves along the surface at a constant speed, for example, during the forced movement of soil particles along the surface of the working body. In this case, in addition to the force of gravity, the force of traction acts on the particle. If we consider the curves along which the particle will exert a constant pressure and the active force will be constant when moving at a constant speed, then such curves will no longer be gravitational.The purpose of the study is to determine a cylindrical surface that provides a constant force of traction or a constant amount of pressure of a material particle moving along it at a constant speed.During the research, curves providing constant pressure at a constant speed of particle movement and curves providing constant traction force at a constant speed of particle movement were considered and their comparisons were made.A comparison of the natural equations of the curves providing a constant pressure with the natural equations of the curves providing a constant traction force showed that these are the same curves, only with different constant coefficients.These curves will retain their properties only if the value of the calculated speed is strictly observed. This is explained by the fact that in the equations of the curves, the speed value is squared, so even its slight deviation from the calculated one causes a significant deviation of the expected results.Key words: cylindrical surface, material particle, speed, traction force, pressure